Analysing the Burden of Healthcare Professionals in Home Care - Bawa, Ramandeep; Sinha, A.K. (Journal of Neonatal Surgery, 2025)
Advancements in technologies and changes in the health care system have resulted in shortened hospital stays, moving the focus of care from hospitals to homes. These services include nursing care, professional caregiving to chronically ill and patients of which substantial numbers are bedridden, immobile or suffer from chronic illnesses like dementia, cancer, heart, lungs, liver, kidney, etc. The burden experienced by family caregivers and paid caregivers is the most important caregiver-related variable in care at home in the care of a chronically-ill person. The extent of subjective burden (which is borne by the caregivers) has a significant impact on the emotional and physical well-being of the family caregivers and the paid caregivers (nurses and general duty assistants), and even influences the mortality of spouse caregivers. In the present study, the researchers interviewed 40 nursing staff, 40 general duty assistants, and 40 family caregivers to analyze the burden they bear instead of their duties in caring for sick patients. The results analyzed were found to be highly significant showing a strong association of home health care workers who provides and hold the bulk of responsibilities and burden as home care staff at their workplace.The output of the study shows the evidence for many national and international agencies to recognize the need to provide support to homecare workers and long –term care in improving their job conditions. The importance of respect, appreciation and the value of understanding the basic job functions cannot be overlooked if retention of workers is required.